2018
DOI: 10.1177/1049909118812193
|View full text |Cite
|
Sign up to set email alerts
|

Health Professionals Perceived Concerns and Challenges in Providing Palliative and End-of-Life Care: A Qualitative Analysis

Abstract: Background: The Institute of Medicine identifies that quality palliative/end-of-life (EOL) care should be provided to patients with serious, life-limiting illnesses and their families by competently prepared health professionals. Purpose: This study assessed perceived concerns of health professionals pertaining to the delivery of palliative/EOL care in the hospital setting. The specific aim was to determine thematic concerns in the delivery of palliative/EOL care which emerged from respondents' impressions of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 19 publications
1
37
0
Order By: Relevance
“…In addition, our findings add to previous studies concluding that the provision of palliative care in an acute care setting, with a care culture emphasizing cure, constitutes a challenge for HCPs. 17,39 The assessment and management of symptoms is a major focus in palliative care, 5,40 and optimal symptom relief is paramount for achieving comfort, maximizing quality of life and preserving patients' self-image, enabling patients to live their lives as well as possible. 41,42 In this study, areas for improvement were identified for all common symptoms causing great suffering, such as pain, nausea, dyspnoea, anxiety, and fatigue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, our findings add to previous studies concluding that the provision of palliative care in an acute care setting, with a care culture emphasizing cure, constitutes a challenge for HCPs. 17,39 The assessment and management of symptoms is a major focus in palliative care, 5,40 and optimal symptom relief is paramount for achieving comfort, maximizing quality of life and preserving patients' self-image, enabling patients to live their lives as well as possible. 41,42 In this study, areas for improvement were identified for all common symptoms causing great suffering, such as pain, nausea, dyspnoea, anxiety, and fatigue.…”
Section: Discussionmentioning
confidence: 99%
“…Concurrently caring for patients with different goals of care represents a challenge for HCPs. [15][16][17] However, studies evaluating quality palliative care in acute or combined care settings are scarce. In addition, several areas for improvement have been identified across settings regarding fundamental cornerstones for palliative care, such as symptom control, communication and shared decision making.…”
Section: Introductionmentioning
confidence: 99%
“…Team discussions of complex situations remained a fundamental aspect of ethics performance, as well as the recommendations on specific issues [23,24] despite the increment of individual skills. Team discussions made the professionals feel more confident and less concerned about the continuous ethical challenges [25] and more capable of meeting the needs of the patient and the family [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…A large descriptive study was previously conducted by members of the PCEC. 8,9 This study determined that specific training for each discipline is needed, but common themes emerged across all disciplines, such as confidence in providing emotional support to patients and families, lack of confidence in providing continuity of care, 8 and need for education on the topics of “cultural influences on care preferences, improving communication between patients/families and providers, education about the differences between palliative and EOL care, and increased competency of health providers in having EOL/goals-of-care discussions.” 9 …”
Section: Design and Methodsmentioning
confidence: 99%
“…8,9 This study determined that specific training for each discipline is needed, but common themes emerged across all disciplines, such as confidence in providing emotional support to patients and families, lack of confidence in providing continuity of care, 8 and need for education on the topics of ''cultural influences on care preferences, improving communication between patients/families and providers, education about the differences between palliative and EOL care, and increased competency of health providers in having EOL/goals-of-care discussions.'' 9 Given this information, the interprofessional team reviewed the APCP's current educational efforts across and within disciplines. It was noted that although the APCP offers unique educational experiences to learners, there was no formal training, learning objectives, dedicated time, or consistency in teaching method or educator.…”
Section: Introductionmentioning
confidence: 99%